Peningkatan Kompetensi Wali Asrama melalui Workshop Berbasis Manajemen Pendidikan Islam di Pesantren Darularafah Raya Deli Serdang - Agustina, Nelly; Salabi, Agus Salim; Zainal, Suadi (Ibrah : Jurnal Pengabdian Kepada Masyarakat, 2022)
Management of student dormitories and prevention of acts of violence in the dormitory environment requires efforts and hard work from the dormitory teachers. This research is to find answers and unravel related materials and the process of implementing the workshop and the impact felt by the dormitory teacherss after the workshop activities. This research is qualitative research with a case study approach. Where researchers are required to obtain data naturally related to the impact experienced by dormitory guardians after workshop activities. So, this research takes no less than three months (from July-October 2022). The data collection technique was carried out by participant observation, interviews with the head of the parenting department, the head of the guidence and consoling department, and the dormitory teachers. To strengthen the data, researchers also conducted a documentation study. All the data obtained was analyzed using the data analysis model proposed by Miles, Huberman, & Saldana, there are: data condensation, data display, and finally drawing conclusions. The results of the study found that the hostel management workshop included: 1) the function of the student dormitory, 2) the skills to identify problems in the student dormitory, 3) planning the activities of the students in implementing the vision/mission of caring for the students, 4) the management of the students, 5) the administration of the student dormitory. While workshops related to the role of dormitory teachers in preventing bullying and intimidation include: 1) persuasive communication patterns for students, 2) planning dormitory activity programs, 3) building coordination and sharing, 4) scheduling muwājahah (face to face) with students/Dyah, 5) conveying advice to strengthen spirituality, 6) enforcing rewards and punishments. The impact of workshop activities for dormitory teachers is an increase in competence in understanding the concept of dormitory management and there are efforts to implement the role of dormitory teachers as parents, brothers, educators, teachers, leaders, managers, administrators, and role models in student dormitories.